Throw away the manual! Reflections on psychotherapy and crime - Manning, Seán; Nicholls, David; Day, Elizabeth (Aporia, 2025)
Aotearoa New Zealand has a high rate of imprisonment, seventh or eighth among 36 OECD countries. The experience of imprisonment, isolation from family and the wider community, the company of a population where violence, misogyny, drugs, risk-taking and rule-breaking are normalised, sees the emergence and practice of a criminal subjectivity. This confers mana, a loyal peer group, mentors and a career, on a population well-endowed with obstacles to these ends.An intoxicating, adaptive, performative subjectivity emerges, is practiced every day, and is not readily given up, accounting for the failure of manualised rehabilitation and treatment models which locate the problem in the individual subject. The prison, a subjectifying machine that perpetuates drug use, violence, poverty, family harm and disenfranchisement, which reduces participation in the wider democracy, mitigates against individual change. Using the philosophy of Michel Foucault, in this paper the authors reflect on method in working with men with extensive prison experience, without relying on the idea of an agentive self – an unlikely fiction among graduates from the prison system.